Literary Traditions: English in Malaysia and Singapore (Column 3) - Quayum, Mohammad Abdul (The Daily Star, Bangladesh, 2014)
Singapore's pragmatic approach towards English has been best summed up by its current Prime Minister, Lee Hsien Loong, in the following statement: “Our mother tongues carry with them values, ancient cultural heritages and a sense of identity. To lose some of this, because we need to speak English, an international language of business and science, is painful, but it is a rational trade-off to make.” Owing to this cosmopolitan outlook and business environment, English has emerged as the pivotal, bridge language in Singapore. In fact, English is so widely used in the country and has become such an integral part of the society, that the concern there, unlike in Malaysia, is, as Thumboo explains, “how to prevent other mother tongues from weakening.”Notwithstanding this fear, which is a valid and legitimate one, especially since language is associated with identity, writers in English have taken full advantage of the situation and have made significant advance in all the genres – poetry, fiction, nonfiction and drama. In the early years of independence, some scepticism was expressed towards literature (poetry in particular) as it was seen as a “luxury” (Lee Kuan Yew's phrase) that Singapore could ill afford. But that scenario has changed as Singapore is now trying to marry commerce with culture and turn itself into an Arts hub. In the manifesto of the Ministry of Information and the Arts, it is stated as a priority objective that, “To ensure sustained growth in the long run, Singapore must forge an environment that is conducive to innovations, new discoveries and the creation of new knowledge.”